The Rupture of Young Muslim Intelligentsia in the Modernization of Indonesia - Yudi Latif (Studia Islamika, 2005)
In March 1966, Army Chief of Staff Soeharto rose to power, taking control of the Indonesian Government. Soeharto's 'New Order' regime inherited a plethora of economic, political and social problems. The New Order came to the conclusion that these crises had evolved as a result of the previous regime's neglect of the economy and lack of concern for social welfare. Economic recovery was viewed as a priority by the new regime for it would tum the attention of the people from politics to the economy thus changing the national outlook from 'politik-sebagai-panglinta'(politics as commander) - as practiced during the Old Order - to 'ekonomi-sebagai-panglima' (economy as commander).DOI: 10.15408/sdi.v12i3.581